"I'm just trying to be tough, okay": Masculine performances of everyday practices. (June 2015) - Collier, Diane R.
Everyday cultural resources that originate outside school offer possibilities for multimodal creativity and identity play, as children consume, transform and produce multimodal texts. In this study, Kyle, a boy in elementary school, fluidly performed social identities and engaged in playful and parodic rescripting of identities and resources from everyday culture, such as professional wrestling and rap music. In this paper, I posit that (1) Kyle and his family understood and experienced professional wrestling in contradictory ways as both taboo and appealing, (2) Kyle's deep knowledge of the genre of professional wrestling as performative text allowed him to use it in playful and parodic ways, (3) this playful approach to wrestling and other masculine identities, made available through Kyle's culture, constitutes a form of improvisation and can be explained as a form of masculine melodrama and (4) the role of audiences is key in the reflexive performance of masculine identities.